Ibret olsun diye . To Make an Example - Sönmez, Necati (Zeze Film, 2007)
Verzio FF Submission In Turkey, the death penalty was abolished in 2002, and the last executions were carried out in 1984. Until then, since the foundation of the republic, a total of 712 people, 15 of them women, had been executed ‘to serve as an example’. Even at times when the death penalty was a hot issue, it was only discussed either around major political cases or based on the argument of ‘unjust executions’. This documentary seeks to address the capital punishment issue through its actual enforcements in Turkey. While wandering round two deserted prisons where many executions were carried out; the film also tries to witness the very last moments of the convicts and raises this question on behalf of the hundreds who died on the gallows: Why did we kill all these people?